Public Infrastructure Accessibility and Property Price Disparities in Jakarta: A Composite Index and Spatial Regression Approach - Anam, Khairul; Sulastri, Ai; Putra, Alvin Anugrah; Sari, Annisa Purnama; Aditama, Friscka Fitri (Politeknik Statistika STIS, 2025)
This study analyzes spatial inequality in public infrastructure accessibility and Property price in Jakarta Province using a Composite Index and spatial econometric modeling. A data-driven spatial approach is employed to examine the distribution of property price and accessibility to health, education, and transportation facilities. Accessibility is measured using the Entropy Weight Method, while spatial inequality patterns are assessed through Moran’s I and Local Indicators of Spatial Association (LISA). Results reveal significant clustering of high property price and accessibility in central Jakarta, contrasted with low values in peripheral areas, indicating pronounced spatial disparities. Furthermore, Geographically Weighted Regression (GWR) and the Spatial Lag Model (SLM) demonstrate that improved accessibility is positively associated with higher property price, although the magnitude of this effect varies spatially. These findings provide empirical evidence to support data-based spatial planning and infrastructure development policies aimed at reducing urban spatial disparities and promoting more equitable urban growth in Jakarta.